Diagnostic power of laboratory tests for hereditary spherocytosis: a comparison study in 150 patients grouped according to molecular and clinical characteristics - Bianchi, Paola (Ferrata Storti Foundation, 2012)
BACKGROUND: The laboratory diagnosis of hereditary spherocytosis commonly relies on NaCl-based or glycerol-based red cell osmotic fragility tests; more recently, an assay directly targeting the hereditary spherocytosis molecular defect (eosin-5′-maleimide-binding test) has been proposed. None of the available tests identifies all cases of hereditary spherocytosis. DESIGN AND METHODS: We compared the performances of the eosin-5′-maleimide-binding test, NaCl-osmotic fragility studies on fresh and incubated blood, the glycerol lysis test, the acidified glycerol lysis test, and the Pink test on a series of 150 patients with hereditary spherocytosis grouped according to clinical phenotype and the defective protein, with the final aim of finding the combination of tests associated with the highest diagnostic power, even in the mildest cases of hereditary spherocytosis. RESULTS: The eosin-5′-maleimide-binding test had a sensitivity of 93% and a specificity of 98% for detecting hereditary spherocytosis: the sensitivity was independent of the type and amount of molecular defect and of the clinical phenotype. The acidified glycerol lysis test and Pink test showed comparable sensitivity (95% and 91%). The sensitivity of NaCl osmotic fragility tests, commonly considered the gold standard for the diagnosis of hereditary spherocytosis, was 68% on fresh blood and 81% on incubated blood, and further decreased in compensated cases (53% and 64%, respectively). The combination of the eosin-5′-maleimide-binding test and acidified glycerol lysis test enabled all patients with hereditary spherocytosis to be identified. The eosin-5′-maleimide-binding test showed the greatest disease specificity. CONCLUSIONS: Each type of test fails to diagnose some cases of hereditary spherocytosis. The association of an eosin-5′-maleimide-binding test and an acidified glycerol lysis test enabled identification of all patients with hereditary spherocytosis in this series and, therefore, represents a currently effective diagnostic strategy for hereditary spherocytosis including mild/compensated cases.